Radioprotectant screening for cryocrystallography. - Southworth-Davies, R; Garman, E (2007)
Radiation damage continues to present a problem to crystallographers using cryocooled protein crystals at third-generation synchrotrons. Free-radical scavengers have been suggested as a possible means of reducing the rate of this damage. The screening of a large number of potential radioprotectants was undertaken with an online microspectrophotometer using cystine and cysteine to model protein disulfide bonds and thiol groups, respectively. Oxidized alpha-lipoic acid was tested as a possible model disulfide bond. The evidence for the effectiveness of ascorbate as a radioprotectant was strengthened, and quinone, 2,2,6,6-tetramethyl-4-piperidone, and reduced dithiothreitol showed promise as radioprotectants.